Psychosocial Adaptation in Dealing with Psychosocial Problems on Family Caregivers of Schizophrenic Patients: A Systematic Review - Budiarto, Eka; Keliat, Budi Anna; Mustikasari, Mustikasari (Universitas Aisyah Pringsewu, 2023)
Schizophrenia is a serious mental disorder that requires long-term care and treatment. The treatment requires caregivers who may come from the family. A caregiver's daily tasks can be overwhelming, leading to psychosocial problems. This study aims to identify the effectiveness of psychosocial adaptation interventions in overcoming psychosocial problems in family caregivers of schizophrenic patients. This study used a systematic review approach. The literature search was sourced from five databases: Wiley Online Library, ScienceDirect, ProQuest, EMBASE, and Sage Journals. The keywords used were family caregiver, schizophrenia patient, psychosocial adaptation, and psychosocial problem. The results of a literature search obtained 448 articles then were screened with the criteria of articles published in 2018-2023, open access, full-text articles, original articles with a randomized controlled trial study design, discussing psychosocial adaptation interventions and psychosocial problems in schizophrenic family caregivers, and English. The results of the article screening obtained six articles, and critical appraisal was carried out using the JBI Critical Appraisal Checklist for Randomized Controlled Trials. All of them were included in grade A ( 90%). Based on the results, psychosocial adaptation interventions effectively dealt with family caregivers' psychosocial problems, including signs of depression, anxiety, stress, self-stigma, psychological burden, emotions, feelings of worthlessness, and powerlessness. Therefore, psychosocial adaptation interventions for schizophrenia family caregivers could be conducted comprehensively by telephone or spiritual approach, involving direct contact with patients, families, and communities. With optimal involvement by family caregivers by focusing on positive aspects and goals that the family caregiver wants to achieve, the role of accompanying the care and treatment of schizophrenic patients can be achieved.